Early Care and Education Teacher's Role in Obesity Prevention and Healthy Development of Young American Indian Children. (January 2019) - Kracht, Chelsea L.; Sisson, Susan B.; Walker, Devon; Kerr, Kelly; Stephens, Lancer; Anderson, Amber; Seward, Julie; Weedn, Ashley E.; Cheney, Marshall; Copeland, Kristen; Salvatore, Alicia L.; Jacob, Audrey; et al.
Introduction: The purpose of this study was to develop an understanding of how stakeholders, specifically early care and education (ECE) teachers, perceive their role in the development of young American Indian children, and envision working with health care providers and parents in order to enhance children's health.Methodology: Twenty tribally affiliated ECE teachers from Oklahoma participated in interviews. Thematic analysis was conducted, and three main themes, each with two to three subthemes, emerged.Results: Teachers felt that nutrition and physical activity were important to children's health. Teachers had little professional interaction with health care providers but desired more. Parental empowerment was conveyed as essential to actualize positive changes in their child's behavior.Discussion: Teachers of tribally affiliated ECE centers are important stakeholders in promoting the health and well-being of young American Indian children. Additional efforts are needed to more effectively integrate teachers and nurses in order to create effective interventions. We propose a stakeholder partnership to guide the development of future interventions.